ANALISIS NILAI EFISIENSI BANK DOMESTIK DAN BANK ASING DENGAN METODE PARAMETRIK STOCHASTIC FRONTIER ANALYSIS (Studi kasus pada Bank Domestik dan Bank Asing di Indonesia periode tahun 2013-2017) - Swaskarina, Neisya Hafizha; Pangestuti, Irene Rini Demi (Diponegoro Journal of Management, 2019)
This research was conducted to analyze the value of banking efficiency in both domestic and foreign banks in Indonesia over a period of five years, 2013-2017. Efficiency is a parameter that can be used as a basis for measuring the performance of a bank. Combining banking efficiency can use traditional methods and border methods.This study uses counting parameters to calculate banking efficiency with the stochastic frontier analysis (SFA) method. The SFA method, presented in the form of a percentage, is increasingly valued at 100% choosing banks that make them more efficient and healthy. By knowing the results of bank efficiency values, it is hoped that banks can improve their supervisory strategies and make certain policy decisions. The sampling technique used was purposive sampling, obtained as many as 15 sample companies, namely 11 groups of domestic banks and 4 foreign banks. Research conducted during the five years of research, namely 2013-2017.The results of calculations with the Stochastic Border Analysis model, the efficiency figures that appear almost entirely completed 100%. This shows a high level of efficiency carried out by Domestic Banks and Foreign Banks. The highest efficiency at the Domestic Bank was generated by PT Bank Mandiri Persero Tbk in 2017 with an efficiency value of 94.64%, and Foreign Banks generated by Standard Chartered PLC in 2017 with an efficiency value of 93.87%